Electronic communication during nonwork time and withdrawal behavior: An analysis of employee cognition-emotion-behavior framework from Chinese cultural context - Liao, Ganli; Li, Miaomiao; Yin, Jielin; Wang, Qianqiu (Frontiers in Psychology, 2022)
Although a large number of literatures have explored the relationship between electronic communication during nonwork time and individual perception and behavior under the Western culture background, we still have some limitations on this topic under the cultural background of collectivism, dedication and “Guanxi” in China. Different from Western organizations, Chinese employees tend to put work first and are more inclusive of handling work tasks during nonwork time. This type of communication during nonwork time can significantly affect employees’ cognition, emotion and behavior. From the perspective of Job Demands-Resources theory, this study constructs a double-edged (U-shaped) model between electronic communication during nonwork time and employee withdrawal behavior. Sample data were collected from 516 employees with clear working time boundaries in China. The results indicate that electronic communication during nonwork time has a U-shaped effect on employee withdrawal behavior and an inverted U-shaped effect on employee’s cognition, namely job engagement. Job engagement plays a mediating role between them. Moreover, regulatory emotional self-efficacy has a moderating effect on the relationship between electronic communication during nonwork time and job engagement. These findings not only provide theoretical and practical implications for managers and employees on how to reduce withdrawal behaviors, but also advance our understanding of electronic communication during nonwork time in Chinese cultural context.